Forget me not - Derrick, Alyson (Simon and Schuster BFYR, 2023)
Eighteen-year-old Stevie and Nora's plan to abandon their conservative small town for California so they can be together is shattered when a terrible fall steals every trace of Stevie's relationship with Nora from her memory.